2020
DOI: 10.3390/antiox9020133
|View full text |Cite
|
Sign up to set email alerts
|

Polyurea Dendrimer Folate-Targeted Nanodelivery of l-Buthionine Sulfoximine as a Tool to Tackle Ovarian Cancer Chemoresistance

Abstract: Ovarian cancer is a highly lethal disease, mainly due to chemoresistance. Our previous studies on metabolic remodeling in ovarian cancer have supported that the reliance on glutathione (GSH) bioavailability is a main adaptive metabolic mechanism, also accounting for chemoresistance to conventional therapy based on platinum salts. In this study, we tested the effects of the in vitro inhibition of GSH synthesis on the restoration of ovarian cancer cells sensitivity to carboplatin. GSH synthesis was inhibited by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Previous studies have reported that the combination of Ce6 and BSO via polymer nanoparticles significantly enhances the effect of photodynamic therapy and inhibits cancer progression compared to therapy without BSO. In ovarian cancer, BSO sensitizes cancer cells to carboplatin therapy via utilizing folate-targeted polyuria dendrimer nanoparticles, which simultaneously decrease the cytotoxicity to normal cells . These studies indicate that the combination of BSO and traditional chemotherapy drugs via nanodrug delivery systems is an effective method for cancer therapy.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have reported that the combination of Ce6 and BSO via polymer nanoparticles significantly enhances the effect of photodynamic therapy and inhibits cancer progression compared to therapy without BSO. In ovarian cancer, BSO sensitizes cancer cells to carboplatin therapy via utilizing folate-targeted polyuria dendrimer nanoparticles, which simultaneously decrease the cytotoxicity to normal cells . These studies indicate that the combination of BSO and traditional chemotherapy drugs via nanodrug delivery systems is an effective method for cancer therapy.…”
Section: Discussionmentioning
confidence: 92%
“…In ovarian cancer, BSO sensitizes cancer cells to carboplatin therapy via utilizing folate-targeted polyuria dendrimer nanoparticles, which simultaneously decrease the cytotoxicity to normal cells. 42 These studies indicate that the combination of BSO and traditional chemotherapy drugs via nanodrug delivery systems is an effective method for cancer therapy. Pt/BSO-MS-HA not only consumed GSH by releasing DSCP but also suppressed the synthesis of GSH by BSO in our study.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In liver cancer, SSA was reported to inhibit CD133-positive HCC cells and sensitize HCC cells towards chemotherapy [ 37 ]. Furthermore, the direct ablation of GSH synthesis by BSO has also been demonstrated to exert therapeutic effects in various types of cancer cells [ 38 , 39 ]. In this study, we demonstrated that depletion of GSH and cysteine by BSO and SSA in HCC cells could partially suppress the aggressive phenotypes induced by GSH and NAC.…”
Section: Discussionmentioning
confidence: 99%
“…In order to overcome this limitation, interesting studies have been carried out using polymeric nanoparticles loaded with BSO and other anticancer agents [Cruz A, Mota P et al 2020].…”
Section: Gsh Biosynthesis Inhibitorsmentioning
confidence: 99%